2020
DOI: 10.3390/cancers12123673
|View full text |Cite
|
Sign up to set email alerts
|

S100A10 Has a Critical Regulatory Function in Mammary Tumor Growth and Metastasis: Insights Using MMTV-PyMT Oncomice and Clinical Patient Sample Analysis

Abstract: S100A10 (p11) is a plasminogen receptor that regulates cellular plasmin generation by cancer cells. In the current study, we used the MMTV-PyMT mouse breast cancer model, patient tumor microarray, and immunohistochemical (IHC) analysis to investigate the role of p11 in oncogenesis. The genetic deletion of p11 resulted in significantly decreased tumor onset, growth rate, and spontaneous pulmonary metastatic burden in the PyMT/p11-KO (knock-out) mice. This phenotype was accompanied by substantial reduction in Ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…We proposed that S100A10-dependent plasmin generation plays a critical role in the movement of macrophages to the tumor site and, therefore, S100A10 was essential and sufficient for macrophage migration to tumor sites. Next, we established the MMTV-PyMT (mouse mammary tumor virus-polyoma middle tumor-antigen) transgenic breast cancer model in wild-type and S100A10 knockout mice and used this double transgenic model to investigate the role of S100A10 in breast cancer malignancy [ 188 ]. The MMTV-PyMT model is a significant advance in the study of oncogenesis because it recapitulates all the phases of oncogenesis.…”
Section: Role Of the Anxa2/s100a10 Heterotetramer In Cancermentioning
confidence: 99%
“…We proposed that S100A10-dependent plasmin generation plays a critical role in the movement of macrophages to the tumor site and, therefore, S100A10 was essential and sufficient for macrophage migration to tumor sites. Next, we established the MMTV-PyMT (mouse mammary tumor virus-polyoma middle tumor-antigen) transgenic breast cancer model in wild-type and S100A10 knockout mice and used this double transgenic model to investigate the role of S100A10 in breast cancer malignancy [ 188 ]. The MMTV-PyMT model is a significant advance in the study of oncogenesis because it recapitulates all the phases of oncogenesis.…”
Section: Role Of the Anxa2/s100a10 Heterotetramer In Cancermentioning
confidence: 99%
“… 20 In a study of breast cancer, S100A10 expression was significantly elevated in high-grade, triple-negative tumours and tumours with a high proliferative index. 8 In a study of lung squamous cell carcinoma tissue, S100A10 levels were significantly associated with higher TNM stage, tumour size, lymphatic invasion and lymph node metastasis. 11 The results of these studies were consistent with literature reporting that serum S100A10 is related to cancer characteristics.…”
Section: Discussionmentioning
confidence: 97%
“… 5 Previous reports have indicated that S100A10 acts as an oncoprotein in ovarian cancer, gastric cancer, breast cancer and renal cell cancer. 6 9 In lung cancer, S100A10 is likely involved in the progression of invasion and metastasis through regulation of plasmin production and subsequent plasmin-dependent stimulation of matrix metalloproteinase (MMP)-2 and MMP-9. 10 A previous report demonstrated that S100A10 tissue levels were higher in cancer tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypes of plasminogen and Plg-R KT −/− mammary glands are also distinct, in that plasminogen deficiency results in delays in ductal development during puberty [ 82 ] that are not observed in Plg-R KT −/− glands [ 83 ]. Recently, the loss of S100A10 has been shown to impair ductal development during the early stages of mammary development [ 84 ]. Thus, mammary development provides an example of the utilization of multiple plasminogen receptors at distinct steps in a physiologic process.…”
Section: Lactationmentioning
confidence: 99%